Will the Remote Work Revolution Undermine Progressive State Income Taxes? - David R. Agrawal; Kirk J. Stark (Center for Economic Studies and ifo Institute (CESifo), 2022)
The remote work revolution raises the possibility that a larger segment of the population will be able to sever the geographic linkage between home and work. What are the taxing rights of states as to nonresident remote workers? May a state impose income taxes on nonresident employees only to the extent they are physically working within the state? Does state taxing power extend to all income derived from in-state firms, including wages paid to those who never set foot in the state? Standard sourcing rules attribute wage income to the employee's physical location. In the presence of remote work, however, rigid adherence to this physical presence rule could intensify the progressivity-limiting dynamics of federalism by reducing the costs to households of exploiting labor income tax differentials across jurisdictions. We document the rise of remote work and the status of state-level income tax progressivity as well as its evolution over time. We consider how alternative legal rules for the sourcing of income can affect telework-induced mobility, but conclude that, regardless of which sourcing regime prevails in coming legal battles, the rise of remote work is likely to limit redistribution via state income taxes. While some sourcing rules may better preserve progressivity in the short term than others, the more fundamental threat to progressive state tax regimes derives from remote work's long-term erosion of the benefits of urban spatial clustering. To the extent that the nation's productive cities lose their allure as centers of agglomeration and the wages of high-skilled workers in these cities fall, the ability of their host states to pursue redistributive tax policies will likely be constrained. These deglomeration effects will arise regardless of how state taxing rights are adapted for the remote work era, and therefore may carry with them implications for income tax progressivity at the federal level.
Keywords: H20; H70; J60; K30; R50; 330; income tax; remote work; sourcing rules; progressivity